Evaluation of Eustachian Tube Function in Mucosal Chronic Otitis Media: A Cost-Effective Method for Developing Countries - Bhat, Vikram Kemmannu; Marimuthu, Gowri Sankar; Herur, Kiran; Yadav, Mona (Annals of Otology and Neurotology, 2018)
Background In the developing nations, the sinonasal region is routinely screened in chronic otitis media, but Eustachian tube is not as it is not cost-effective. Hence, we innovated an inexpensive device named Eustachian barotubometer.Materials and Methods A prospective case–control study was performed on mucosal type of chronic otitis media and traumatic tympanic perforation (100 cases each). Eustachian tube function was assessed by the Eustachian barotubometer (forced and physiological opening) and nasopharyngoscopy.Results Eustachian tube dysfunction was found to be five times higher in cases than controls. Both forced opening function and physiological opening function were poorer in cases than controls. However, the difference was statistically significant only in physiological opening function (p = 0.003). Among the cases with dysfunctional tubes, 86.7% were hypofunctional, whereas 13.3% were totally blocked.Conclusion Eustachian tube function was affected in 15% of cases of mucosal chronic otitis media as compared with controls in this study. This novel device could be conveniently used to help decide the right time to undertake middle ear surgery.
Keywords: chronic otitis media; Eustachian tube function; middle ear